2021
DOI: 10.3847/1538-4357/ac111e
|View full text |Cite
|
Sign up to set email alerts
|

Migrating Planets into Ultra-short-period Orbits during Episodic Accretion Events

Abstract: Ultra-short-period (USP) planets reside inside the expected truncation radius for typical T Tauri disks. As a result, their current orbital locations require an explanation beyond standard disk migration or in situ formation. Modern theories of planet-disk interactions indicate that once a planet migrates close to the disk's inner truncation radius, Type I torques vanish or switch direction, depending on the stellar and disk conditions, so that the planet is expected to stop its orbital decay and become trappe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 107 publications
(101 reference statements)
0
8
0
Order By: Relevance
“…showed that the initial obliquity needs to be about ∼ 20 − 40 • to form the USP, which is similar to the required tilts in the top row of Figure 9, corresponding to the inner-aligned configuration. Moreover, if the USP formed during episodic accretion events (Becker et al 2021), the planet tends to arrive early because the USP can migrate in a short timescale with this mechanism. This indicates a large initial inclination of the outer planet (e.g., ∼ 34 • if arrived around 10 Myr).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…showed that the initial obliquity needs to be about ∼ 20 − 40 • to form the USP, which is similar to the required tilts in the top row of Figure 9, corresponding to the inner-aligned configuration. Moreover, if the USP formed during episodic accretion events (Becker et al 2021), the planet tends to arrive early because the USP can migrate in a short timescale with this mechanism. This indicates a large initial inclination of the outer planet (e.g., ∼ 34 • if arrived around 10 Myr).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dynamical migrations could lead to the configuration of an aligned outer planet with a misaligned inner planet (Petrovich et al 2019;Pu & Lai 2019). Finally, the migration during episodic accretion (Becker et al 2021) can also contribute to the formation of USPs and the migration timescale is much shorter than the other mechanisms mentioned above.…”
Section: Specific Examplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Planet obliquity tides can also produce USP planets with low initial semimajor axes (a  0.05 au ;. Moreover, during episodic accretion events, the planet migrates into a USP orbit in a very short timescale by headwind torques (Becker et al 2021).…”
Section: Introductionmentioning
confidence: 99%
“…USP planets (defined as those with orbital periods of less than a day) occur around ∼0.5% of G-dwarf stars (Sanchis-Ojeda et al 2014), and when they occur in STIPs, they often exist in apparently decoupled dynamical modes as compared to the rest of the system, sometimes in a coplanar configuration (ex: Swift et al 2013;Becker et al 2015;MacDonald et al 2016) and sometimes in a misaligned configuration (e.g., Rodriguez et al 2018;Quinn et al 2019). Since the (sometimes near-resonant) geometry of STIPs indicates that they formed via disk migration (Rein 2012;Batygin 2015;Deck & Batygin 2015), the presence of an interior planet in a different dynamical mode requires an explanation (Petrovich et al 2019;Pu & Lai 2019;Becker et al 2021). Dai et al (2018) noted that USP planets' orbital inclinations have a wider range of values with respect to nearby, exterior planets than do similar but longer-period planets.…”
Section: Introductionmentioning
confidence: 99%